A weak Galerkin finite element method for parabolic singularly perturbed convection-diffusion equations on layer-adapted meshes - Suayip Toprakseven; Seza Dinibutun (Electronic Research Archive)
In this paper, we designed and analyzed a weak Galerkin finite element method on layer adapted meshes for solving the time-dependent convection-dominated problems. Error estimates for semi-discrete and fully-discrete schemes were presented, and the optimal order of uniform convergence has been obtained. A special interpolation was delicately designed based on the structures of the designed method and layer-adapted meshes. We provided various numerical examples to confirm the theoretical findings.